IMPLIKASI INISIATIF PERCERAIAN TERHADAP HAK NAFKAH ISTRI - Najichah Najichah (Journal of Islamic Studies and Humanities, 2020)
AbstractDivorce is the case most frequently submitted to the Religious Courts in Indonesia. This paper discusses how the divorce initiative has implications for the wife's right to post-divorce income. There are differences regarding the wife's right to post-divorce income based on who took the initiative to file for the divorce. In a divorce on the husband's initiative, based on the Compilation of Islamic Law, the husband is obliged to provide the wife's rights in the form of post-divorce income. Whereas for the divorce initiative originating from the wife, there is no obligation for the husband to give the wife the right to post-divorce income. Legal progressiveness emerges and provides new hope in reforming Islamic family law in Indonesia by punishing husbands to pay for their wives' rights to post-divorce income in divorce cases on the wife's initiative, namely; Jurisprudence of the Supreme Court of the Republic of Indonesia number 137/K/AG/2007, Book II of Guidelines for the Implementation of Duties and Administration of the Religious Courts, Supreme Court Regulation Number 3 of 2017, Circular of the Supreme Court Number 2 of 2019 which are in accordance with the principles of benefit, certainty and legal justice.